(untitled) (Third Sector Social Economic Review, 2025)
This study aims to identify individuals’ attitudes toward telehealth services and to examine whether these attitudes vary according to socio-demographic characteristics. Designed as a descriptive study, the research employed a snowball sampling technique. The sample consisted of 388 voluntary participants aged 18 and over, who can use smartphones. Data were collected through a two-part questionnaire. The first part gathered demographic information, while the second part utilized the "Attitude Towards the Use of Telehealth Services Scale". Data were analyzed using SPSS 23.0. Mann-Whitney U and Kruskal-Wallis H tests were used to examine differences between groups. Participants were generally found to have a moderately positive attitude toward telehealth services. Statistically significant differences were observed based on marital status, employment status, education level, income level, and prior experiences with telehealth services. However, no significant differences were found concerning gender, age, presence of chronic disease, regular medication use, or the presence of a care-dependent individual at home. The findings suggest that attitudes toward telehealth services are shaped by individual, social, and economic factors. It is recommended that inclusive digital health policies be developed to enhance service accessibility and equity.